Art collectors as venture capitalists - Amy Whitaker; Roman Kräussl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
Employing the art-collection records of Burton and Emily Hall Tremaine, we consider whether early-stage art investors can be understood as venture capitalists. Because the Tremaines bought artists' work very close to an artwork's creation, with 69% of works in our study purchased within one year of the year when they were made, their collecting practice can best be framed as venture-capital investment in art. The Tremaines also illustrate art collecting as social-impact investment, owing to their combined strategy of art sales and museum donations for which the collectors received a tax credit under US rules. Because the Tremaines' museum donations took place at a time that U.S. marginal tax rates from 70% to 91%, the near "donation parity" with markets, creating a parallel to ESG investment in the management of multiple forms of value.
Keywords: G11; L31; D31; Z11; 330; Art investment; venture capital; social impact; portfolio management; tax arbitrage